2016
DOI: 10.14260/jemds/2016/1017
|View full text |Cite
|
Sign up to set email alerts
|

Multidetector Ct Angiography v/S Colour Doppler Ultrasonography in the Diagnosis of Peripheral Arterial Diseases of Lower Extremities

Abstract: CONTEXTPeripheral arterial disease of the lower extremity is an important cause of morbidity and affects 10 million people in India. AIMS AND OBJECTIVESThe aims of this study were to assess the colour Doppler ultrasonography findings of lower limbs in patients with peripheral arterial disease by studying the spectral flow pattern and peak systolic velocity and also to assess the severity of stenosis and correlation of severity of stenosis on USG Doppler and MDCT angiography. MATERIALS AND METHODSThe study incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…However, there was an agreement with CTA in only 24/29 (86.2%) cases, thus showing that color Doppler had a sensitivity of 86.2% and specificity of 76.9% in detection of atheromatous changes. ese findings are in agreement with the observations of Dev et al [12] and Peedikayil et al [13] who also found that USG has lower sensitivity and specificity as compared to CTA in detection of luminal narrowing, irregularity, calcification, and atheromatous changes.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, there was an agreement with CTA in only 24/29 (86.2%) cases, thus showing that color Doppler had a sensitivity of 86.2% and specificity of 76.9% in detection of atheromatous changes. ese findings are in agreement with the observations of Dev et al [12] and Peedikayil et al [13] who also found that USG has lower sensitivity and specificity as compared to CTA in detection of luminal narrowing, irregularity, calcification, and atheromatous changes.…”
Section: Discussionsupporting
confidence: 92%
“…[ 12 ] and Peedikayil et al . [ 13 ] who also found that USG has lower sensitivity and specificity as compared to CTA in detection of luminal narrowing, irregularity, calcification, and atheromatous changes.…”
Section: Discussionmentioning
confidence: 99%
“…22 Peedikayil et al did a study of 29 patients with intermittent claudication and showed MDCTA (7.4%) detected more number of lesions of supra-popliteal group of vessels with total occlusion as compared to colour Doppler (6.3%). 24 In this study we found that MDCTA is a very useful modality in detecting peripheral arterial disease of the extremities and as compared to Colour Doppler, MDCTA detected more number of disease segments, MDCTA has the advantages of being more widely available as compared to DSA which is invasive and requires more operator expertise and experience.…”
Section: Limb Wise Distributionmentioning
confidence: 68%
“…12 Tibioperoneal trunk divide into tibial artery(posterior) which pass medially descend to the foot and peroneal pass laterally. 13 This study is planned to compare for diagnosis of various grades of stenosis to assess the benefits and drawbacks of each modality by learning the spectral flow patterns in color Doppler ultrasonography with contrast pacification and diameter reduction in CT angiography. This study will also help in generating local data which can be helpful later on regarding choice of modality for diagnosis of arterial disease in patients with lower limb ischemia.…”
Section: Introductionmentioning
confidence: 99%